2021
DOI: 10.1097/qad.0000000000003155
|View full text |Cite
|
Sign up to set email alerts
|

Mortality disparities among patients with HIV-associated Kaposi's sarcoma in the southern United States

Abstract: Objective:To describe risk factors for mortality in HIV-associated Kaposi's sarcoma in an urban population in Dallas, Texas.Design:Retrospective electronic medical record review of patients with HIV-associated Kaposi's sarcoma.Methods:Electronic medical records were reviewed from 1 January 2009 to 31 December 2018 for patients with a diagnosis of HIV and Kaposi's sarcoma by ICD-9 or ICD-10 codes. Demographics, HIV history, Kaposi's sarcoma history, treatment, and mortality data were collected. Mortality data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…We did not find a difference in KSHV seroprevalence between race/ethnicities to explain the disparities in clinical Kaposi sarcoma previously described [ 8 ]. Previous data have been mixed regarding the relationship between KSHV seroprevalence and race/ethnicity.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…We did not find a difference in KSHV seroprevalence between race/ethnicities to explain the disparities in clinical Kaposi sarcoma previously described [ 8 ]. Previous data have been mixed regarding the relationship between KSHV seroprevalence and race/ethnicity.…”
Section: Discussioncontrasting
confidence: 82%
“…Despite an overall decrease in KS incidence and mortality in the combination antiretroviral therapy (ART) era [ 2 ], certain subpopulations, particularly young Black men in the southern US, have not experienced the same decline in disease and in fact in some regions have faced an increase in KS diagnoses during this time period [ 3–7 ]. This disparity also extends to disease outcomes, as seen among people with HIV with KS in Dallas between 2009 and 2018, where mortality among Black patients was twice as high as non-Hispanic White and Hispanic patients within the same hospital system [ 8 ].…”
mentioning
confidence: 99%
“…Previous studies have shown more than 90% of patients with Kaposi sarcoma in North America were male. 8,10,11 Additionally, epidemiological analysis of KSHV itself has shown a higher prevalence in MSM, particularly those with HIV. 12 While KSHV seroprevalence has been described as 4%-7% in the general blood donating population, it has been as high as 30%-70% in MSM with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a retrospective electronic health record (EHR) review of patients diagnosed with HIV‐associated PEL and/or MCD at Parkland Health, a large, safety‐net hospital system located in Dallas, Texas. Review of EHR charts from January 1, 2009 (start of integrated inpatient and outpatient EHR at Parkland) to December 31, 2018 was conducted using ICD‐9 and ICD‐10 codes similar to our previously published work 8 . Cases were identified if they had a diagnosis of HIV by ICD 9 codes 042 or V08, ICD 10 codes B20 or Z21, and either MCD (identified by ICD‐9 code 238.79 or ICD‐10 code D47.Z2) or PEL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation